Changes in leisure activities of the elderly due to the COVID-19 in Korea - Kim, Eui Jae; Park, Seong Man; Kang, Hyun Wook (Frontiers in Public Health, 2022)
Recreational activities such as physical and social activities are key components of a healthy life for the elderly. Since the outbreak of Corona 19, leisure facilities such as indoor sports facilities, religious facilities, and cultural facilities have been closed, and group activities such as volunteer activities and clubs are also being held under control. These measures are expected to bring about many changes in the leisure activities of the elderly. In this study, an empirical analysis was made on how COVID-19 caused changes in leisure activities of the elderly using national statistical data. For the data analysis, raw data of the “2019 National Leisure Activities Survey” and “2020 National Leisure Activities Survey” conducted by the Ministry of Culture, Sports and Tourism were used, and data of a total of 5,069 elderly people were analyzed. As for the analysis method, the changes in leisure activities of the elderly before and after COVID-19 in terms of participation rate were compared and analyzed. In addition, the changes in leisure activities of the elderly in terms of the type of leisure activities were examined before and after COVID-19 as well. As a result of the analysis, the participation rate in sports activities, hobbies and entertainment activities, and leisure activities increased, while the participation rates in culture and art viewing and participation activities, sports viewing activities, tourism activities, and social activities decreased. In particular, it was found that the proportion of the elderly spending leisure time centered on active and social activities decreased, and the proportion of the elderly consuming leisure time centered on passive activities increased. As a result, it was found that the leisure activities of the elderly are changing passively due to COVID-19. Leisure support policies for active leisure activities of the elderly are likely to be necessary.